Biobased economy available biomass resources in the Czech Republic - Wegscheider, Zdenek; Sabolovic, Mojmir (Journal of Business Economics and Management, 2006)
During the past two decades academia, industry and government have aimed more and more their attention to the phenomenon of a biobased economy providing society with non‐food biobased products. Now developing are biomass industries that make an array of commercial products, including fuels, electricity, chemicals, adhesives, lubricants and building materials, as well as new clothing fibers and plastics. Instead of fossil resources “green” biobased economy uses renewable grown or waste biomass. The lead supplying role to the biobased economy is held by a sector of agriculture, above all the crop production. In this manner an effective limitation of food surplus may occur in the EU market and enhance a value added to all vertical industry. Industrial‐scale production of biobased materials in time with consumers’ changing attitudes towards sustainable economic and social development may affect a wide array of consequences which nowadays can be tediously estimated. Food safety along with food security is one of the hottest issues especially in the United States, knowing that human population and biobased economy compete in using and processing a broad range of agricultural crops. An energy analysis aspect of this caloric relationship among agricultural sector on the supply side and human population and biobased economy on the other – demand side is assumed to represent the principal aim of this study. Consequently, there is the need to evaluate whether a quantity of Czech Crop Output Total is possible to nourish the Czech population and whether there is an available caloric surplus suitable as a biomass resource for biobased economy which is actually taking root.Firstd Published Online: 14 Oct 2010